SYSTEMIC VASCULITIS IN CHILDREN - Iskanova G.Kh., (Лучшие интеллектуальные исследования, 2023)
Systemic vasculitis (SV) is a systemic autoimmune disease of unknown etiology, pathogenetically associated with immunoregulatory disorders that cause hyperproduction of a wide range of organ-nonspecific autoantibodies to various components of the nucleus and immune complexes, causing immuno-inflammatory damage to blood vessels and dysfunction of internal organs [1, 6,8,9,10].